Analysis of Factors Affecting MSME Productivity in Langsa City Tourism Village - Atni, Nurhafifah; Amilia, Suri; Chandra, Riny; Gunanjar, Imam (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the factors influencing the productivity of Micro, Small, and Medium Enterprises (MSMEs) in tourism villages in Langsa City, focusing on capital, human resources (HR), digitalization, and government support. A quantitative approach was employed using a survey method through questionnaires distributed to 58 MSME actors in Cinta Raja Village, selected using saturated sampling. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and F-tests. The results indicate that partially, the HR variable has a positive and significant effect on MSME productivity, while capital, digitalization, and government support show no significant effect. Simultaneously, the four independent variables do not significantly influence MSME productivity. The findings highlight that HR quality is the dominant factor affecting MSME productivity, whereas capital, digital utilization, and government support have not been optimally implemented. This study suggests enhancing HR competence, improving digital literacy, and strengthening government assistance programs to improve MSME productivity in tourism village area.